The Effect of Solvency, Profitability and Liquidity Ratios on Profit Growth in Coal Mining Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Evalina Ani; Haura Adawiyah; Assya Ainun Firanti (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine the effect of solvency, profitability and liquidity on profit growth. The independent variables in this study are solvency as measured by the debt to equity ratio, profitability as measured by the net profit margin, and liquidity as measured by the quick ratio. Meanwhile, the dependent variable in this study is profit growth, profit growth can be calculated from this year's net income minus last year's net profit divided by last year's net profit. This type of research is quantitative research. The sample in this study was selected by purposive sampling method, namely the selection of samples using certain predetermined criteria. Based on the purposive sampling method, a sample of 3 was obtained from 35 mining companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The analytical method used in this study is multiple linear regression analysis using the SPSS version 25 program. The results of this study indicate that solvency has no significant effect on profit growth, and liquidity has no significant effect on profit growth, while profitability has a significant effect on profit growth.